Perbandingan Kinerja Cassandra dan MongoDB Sebagai Backend IoT Data Storage - Adam Kukuh Kurniawan; Eko Sakti Pramukantoro; Primantara Hari Trisnawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The storage solutions for keeping a variety of data is using NoSQL. In the previous research, IoT data storage framework has been developed to solve the problems of large and diverse IoT data by using NoSQL MongoDB and GridFS as the data storage media. But currently there are many NoSQL databases with different implementation mechanisms and storage characteristics. It brings challenges in the NoSQL databases selections that are used as IoT data storage media. In this research will be proposed IoT data storage media using NoSQL Cassandra. The researcher chose NoSQL Cassandra because the implementation mechanism and characteristics of the sessions differ from MongoDB NoSQL. The test is done in terms of functionality on Cassandra in storing data from sensor nodes, as well as in terms of performance of Cassandra and MongoDB in performing insert data text and file operations using Runtime, Throughput, CPU Usage, Memory Usage and DISK I/O parameters. From the results of functionality testing, Cassandra can store heterogeneous data from sensor nodes. For insert data text operations, MongoDB has Runtime, Throughput, and CPU Usage values ​​best compared to Cassandra (runtime 121.2 second, throughput at 1236.7 ops/s, and CPU usage from 4% to 5%). As for insert data file operations, Cassandra has better Runtime, Throughput, and Memory Usage values ​​compared to MongoDB (runtime 86.4 second, throughput at 115.8 ops/s, and disk I/O at 126953 KB)